Evaluation of Morphophysiological and Phytochmical Traits of Different Ecotypes of Salvia multicaulis Vahl. in Hamedan Province, Iran - F Salehi; H Arouiee; HA Naghdi Badi; SH Nemati; SM Tolyat Abulhassani (Institue of Medicinal Plants, ACECR, 2017)
Background: Salvia multicaulis Vahl. a medicinal plant belonging to the Lamiaceae family, has an extensive application in native and traditional medicine. Objective: This research was conducted to investigate diversity of morphophysiological traits and content of essential oil, phenol and flavonoid of Salvia multicaulis ecotypes in different districts of Hamedan province, Iran. Methods: In this study, 11 ecotypes of Salvia multicaulis were collected from different districts of Hamedan Province at the full flowering stage in spring 2016 and were evaluated for their morphophysiological and phytochemical characteristics. The classification of ecotypes was done on the basis of phytochemical and morphophysiological traits by cluster analysis and correlations among quantitative traits was also conducted by Pearson method. Results: Result showed that the essential oil content had positive significant correlation with plant height, inflorescence length, dry matter of flowering branche and essential oil yield. Also there was a positive significant correlation between essential oil yield with receptacle length, flower fresh and dry matter and plant dry matter. The heighes dry weight of flowering branch and flower was related to ecotypes of Lashkardar and west of Hamedan, respectively. The maximum plant dry weight was belong to Yelfan ecotype. The most essential oil content was related to Lashkardar and west of Hamedan ecotypes. Also, the highest content of phenol and flavonoid related to Vehnan ecotype. According to the cluster analysis, 11 ecotypes were divided into two groups. Conclusion: The evaluation of morphophysiological and phytochemical traits showed that there was a considerable variation among different ecotypes of Salvia multicaulis in respect of morphophysiological and phytochemical characteristics.